A place in the sun: farmers’ co-benefits from solar irrigation in Bangladesh - Buisson, Marie-Charlotte; Mitra, Archisman; Hounsa, T.; Habib, Md. A.; Mukherji, Aditi (Elsevier, 2024)
Solar irrigation pumps (SIPs) are gradually replacing diesel pumps in relatively water-intensive agricultural production systems and geographies to reduce carbon emissions from food systems. However, beyond its climate change mitigation potential and fulfillment of Nationally Determined Contributions commitments, the adoption of solar irrigation also has direct co-benefits for farmers. Taking the case of Bangladesh and anchored on primary data collected among solar and diesel pump users, this article analyses the role access to solar irrigation has on household and farm-level outcomes. The propensity score matching and inverse probability matching approaches identify a positive effect of SIP access on food security and profitability from dry-season paddy for adopters. Different transmission channels are explored to explain these co-benefits. Lower costs of irrigation and labor are identified as the strongest pathways. This analysis strengthens the case for investments toward the solarization of agriculture in developing countries where it delivers significant development co-benefits in addition to climate change mitigation benefits. The valuation of the farmers’ co-benefits, along with global climate mitigation impacts, also highlights the potential role of such programs toward climate justice.